INTERNATIONAL PRACTICES OF LARGE ENTERPRISES TAXATION IN THE CONTEXT OF DIGITAL TRANSFORMATION - PhD Umarov Bakhodir Sultonovich (Modern American Journals, 2025)
This article investigated the international practice of taxing large enterprises. It conducted a comparative analysis of the criteria for determining large enterprises, types and rates of taxes in different countries, and tax optimization strategies.
Keywords: Tax, taxation systems, large enterprise taxation, transfer pricing, criteria of large enterprises